Vlsi interconnection network for numerical solution of two point boundary value problems - Suros, R.; Montagne, E. (International journal of computer mathematics, 1989)
We present the shooting parallel method implemented in systolic systems to solve Ordinary Differential Equations, taking advantage of the fact that this method may be greatly parallelised and that it generates diagonal or triangular sparse matrices. The original problem is partitioned into subproblems whose individual size fit available systolic network dimensions. The network sizes depend on the order of the matrices used. The fitted technique is applied to halve the size of systolic networks used and therefore the sizes of networks are halved. We propose an organization scheme for the network interconnections.